Multiple Intelligence Integration: Enhancing Social Studies Learning Outcomes in Indonesian Primary Schools - Hardiyati, Mikyal; Fitriati, Resti (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
Traditional social studies instruction in Indonesian primary schools often employs one-size-fits-all approaches that fail to accommodate diverse student learning preferences, resulting in suboptimal academic achievement and limited student engagement. This study aims to examine the effectiveness of Multiple Intelligence (MI) integration in enhancing social studies learning outcomes among Grade 4-6 students in Indonesian primary schools. A quasi-experimental design was employed with 120 students from three schools in Jakarta, comparing MI-integrated instruction with conventional teaching methods over 12 weeks. Data were collected through pre-post achievement tests, learning engagement surveys, and classroom observations. Results demonstrated significant improvements in academic performance (p<0.05), with experimental groups showing 23% higher achievement scores and increased participation rates across all intelligence domains. Students exhibited enhanced critical thinking skills, cultural awareness, and collaborative learning behaviors. The findings suggest that MI integration provides a viable framework for differentiated social studies instruction, offering practical implications for curriculum developers and educators to create more inclusive and effective learning environments that honor diverse student strengths and learning pathways.